Cell encapsulation in a magnetically aligned collagen–GAG copolymer microenvironment. (1st January 2015) - Novak, Tyler; Voytik-Harbin, Sherry L.; Neu, Corey P.
Graphical abstract: Abstract: Engineered tissue microenvironments impart specialized cues that drive distinct cellular phenotypes and function. Microenvironments with defined properties, such as mechanical properties and fibril alignment, can elicit specific cellular responses that emulate those observed in vivo. Collagen- and glycosaminoglycan (GAG)-based tissue matrices have been popularized due to their biological ubiquity in a broad range of tissues and the ability to tune structure and mechanical properties through a variety of processes. Here, we investigate the combined effects of static magnetic fields, and GAG and cell encapsulation, on the structure (e.g. collagen fibril orientation) and material properties of collagen matrices. We found that magnetic fields align the collagen–GAG matrix, alter equilibrium mechanical properties and provide a method for encapsulating cells within a three-dimensional aligned matrix. Cells are encapsulated prior to polymerization, allowing for controlled cell density and eliminating the need for cell seeding. Increased relative GAG concentrations reduced the ability to magnetically align collagen fibrils, in part through a mechanism involving increased viscosity and polymerization time of the collagen–GAG solution. This work provides a functional design space for the development of pure collagen and hybrid collagen–GAG matrices in the presence of magnetic fields. Additionally, this work shows that magnetic fields are effective for the fabrication of collagen constructs with controlled fibril orientation, and can be coupled with GAG incorporation to modulate mechanical properties and the response of embedded cells.